THE EFFECT OF ISLAMIC CORPORATE SOCIAL RESPONSIBILITY ON FINANCIAL PERFORMANCE AND REPUTATION OF ISLAMIC BANKS IN INDONESIA - Alif Maulana Bachtiar; Agung Abdullah (Program Studi Ekonomi Syariah, Universitas Pangeran Diponegoro Nganjuk, 2025)
This study purpose to determine the influence of ICSR on financial performance and reputation of Islamic commercial banks in Indonesia on period 2019-2023. This study reveals how much impact the implementation of ICSR has on Islamic banks. The data sourced from annual reports of Islamic banks, this study uses multiple linear regression models. The number of samples in this study is 9 Islamic commercial banks registered by Indonesia Financial Service Authority (OJK). By using SPSS 23 software analysis tools, the result is ICSR has significantly affect the reputation of Islamic banks due to their foundational principles to contribute to the society in accordance to the principles of Islamic philanthropy. But the financial performance variable, ICSR showed no significant influence due of performance because of performance for some reason which could relate to ICSR initiatives focused on Islamic Phylantropi based aspects, does not directly affect financial metrics (profitability, ROA) and focus on short-term financial data, missing the delayed payoff of ICSR. This research takes a more actual observation year than the previous research and uses more accurate indicators in accordance with the regulations of the regulators.